Efficacy comparison of Kirschner-wire tension band combined with patellar cerclage and anchor-loop plate in treatment of inferior patellar pole fracture - Du, Bing; Ma, Teng; Bai, Huanan; Lu, Yao; Xu, Yibo; Yang, Yanling; Zhang, Kun; Li, Zhong; Li, Ming (Frontiers in Bioengineering and Biotechnology, 2022)
Abstract Objective: This study aimed to compare the biomechanical stability and clinical efficacy of the Anchor Loop Plate ( ALP ) and Kirschner wire tension band in treating inferior pole patellar fracture. Results： The biomechanical analysis of the finite element model showed that the maximum displacement of the K-wire group was 2.16 times that of the ALP group. The maximum stress of the K-wire group was 1.59 times that of the ALP group. The maximum stress of the pole bone in the K-wire group was 17.74 times that of the ALP group. The average follow-up time of the K-wire group and anchor loop plate group was similar ( P > 0.05 ); the average age of the two groups was similar ( P > 0.05 ); the average operation time was similar ( P > 0.05 ). The final knee joint activity of the anchor loop plate group was significantly greater than that of the Kirschner wire K-wire group ( P < 0.05 ). The Bostman patellar fracture function score of the anchor loop plate group was significantly better than that of the Kirschner wire K-wire group at 3 and 9 months after operation ( P < 0.05 ). Postoperative complications of the two groups: 1 case ( 3.6 % ) of the anchor loop plate group had internal fixation stimulation complications, 2 cases ( 6.6 % ) of the K-wire group had internal fixation stimulation complications, 1 case ( 3.3 % ) of infection, 6 cases ( 20.0 % ) of internal fixation failure. Conclusions： The anchor loop plate and tension band were tested under 500 N without failure, indicating that the newly designed anchor loop plate is safe in mechanical structure. Moreover, the anchor loop plate has a better surgical effect than traditional surgery in terms of biomechanical stability, postoperative complications, secondary surgery and knee joint function. This technique is an effective treatment for the patellar fracture.